Water footprints of milk production: a case study in the Moga District of Punjab, India. Project report submitted to Nestle Ltd. under the project "Measuring the water footprints of milk production: contributions to livelihood benefits and sustainable water use in the Moga District in Punjab, India? - Amarasinghe, Upali A.; Smakhtin, Vladimir U.; Sharma, Bharat R.; Eriyagama, Nishadi (International Water Management Institute, 2010)
A project report submitted to Nestle Ltd. under the project "Measuring the water footprints of milk production: contributions to livelihood benefits and sustainable water use in the Moga District in Punjab, India.? This report assesses the water footprints of milk and crop production, their impacts and options of mitigating them. The major objectives of this report are: To assess water availability and use in agriculture in the Moga District of Punjab State, to examine the contribution of the different agricultural water uses to the over all unsustainable water extraction, and its impact on the WFP of milk and crops; To assess surface water and groundwater use of major crops (e.g., rice, wheat and fodder crops) and in milk production, with a focus on feed and fodder and direct water use for dairy cattle; and To propose improved water management practices that farmers can adopt to reduce WFP, and enhance water productivity and conservation, thus contributing to long-term sustainable water use in the region.